PENGARUH MEDIA PUZZLE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SD NEGERI 071162 ESIWA - Tina Rohani Gea; Ratna Natalia Mendrofa; Otilina Gulo; Lestari Waruwu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low learning outcomes of students in the Indonesian Language subject, which were caused by teacher-centered learning, low student participation, and the suboptimal use of instructional media. This study aimed to determine the effect of Puzzle media on the learning outcomes of fifth-grade students in the Indonesian Language subject at SD Negeri 071162 Esiwa. This research employed a quantitative approach using a pre-experimental method with a One-Group Pretest–Posttest Design. The population as well as the sample consisted of 25 fifth-grade students selected using the saturated sampling technique. Data were collected through pretest and posttest instruments that had been tested for validity and reliability. The data were analyzed using the normality test, N-Gain test, and hypothesis testing with the assistance of SPSS version 26. The results showed that the data were normally distributed, the average student learning outcomes increased after the implementation of Puzzle media, and the N-Gain score was 66.85, which falls into the moderate category, indicating an improvement in students' learning outcomes. Furthermore, the hypothesis testing revealed a calculated t-value of 18.097 with a significance value of 0.000 (< 0.05), indicating that the alternative hypothesis was accepted while the null hypothesis was rejected. Therefore, it can be concluded that Puzzle media has a positive and significant effect on the learning outcomes of fifth-grade students in the Indonesian Language subject at SD Negeri 071162 Esiwa.